PENGARUH MUTU PELAYANAN TERHADAP TINGKAT KEPUASAN PASIEN RADIOTHERAPY DI RSU VINA ESTETICA MEDAN TAHUN 2021 - Siti Khoiroh Harahap; Razia Begum Fitriani; Razia Begum Suroyo (Jurnal Kesehatan dan Fisioterapi, 2023)
The results of the initial survey showed that patient satisfaction in 2019 the patient satisfaction index in the Radiotherapy room at RSU Vina Estetica only reached 70%. This study aims to analyze the effect of service quality on the level of satisfaction of radiotherapy patients at RSU Vina Estetica Medan in 2021. This research is a quantitative study with a cross sectional study design conducted at RSU Vina Estetica which took place from November - December 2021. The study population was all Radiotherapy patients at RSU Vina Estetica Medan who visited from January to October 2021 were 199 people. With a sample of 67 people. The survey data were analyzed using Chi Square test and logistic regression. The results of the univariate study showed that of the 67 respondents, most of the respondents aged 66-55 years were 39 (58.3%) and had a high school education level, namely 31 (46.3%). Bivariate analysis showed that there was an effect of officer communication (p=0.001), officer responsiveness (p=0.002), environmental cleanliness and comfort (p=0.000), pain management (p=0.001), communication about treatment (p=0.000), communication before the patient went home (p=0.005). on the level of satisfaction of radiotherapy patients at RSU Vina Estetica Medan in 2021, namely the officer's communication variable. The results of the multivariate analysis are the variables that most influence the level of satisfaction of radiotherapy patients at RSU Vina Estetica Medan in 2021, namely the officer communication variable. Suggestions in this study are that it is hoped that the results of this study can be used as input for changing communication habits so far.  Keywords: Service Quality, Patient Satisfaction